Inorganic water-based phosphate metal anti-corrosion nano coating and preparation method thereof

By adding ceria nanoparticles and dispersants to the nano-anti-corrosion coatings, combining environmentally friendly water-based polyurethane resin and phosphate materials, the problems of insufficient dispersion, construction difficulty and environmental protection performance of nano-anti-corrosion coatings are solved, and high performance and Environmentally friendly inorganic aqueous phosphate metal anticorrosion nanocoating.

CN119463675APending Publication Date: 2025-02-18CHINA TOWER CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411672802.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Existing nano-anti-corrosion coatings have problems with dispersion, difficulty in construction and insufficient environmental protection performance.

Method used

The use of inorganic aqueous phosphate metal anticorrosion nanocoatings is improved by adding ceria nanoparticles and dispersants to the coating, and the use of environmentally friendly water-based polyurethane resin and phosphate materials. Reduce the content of volatiles and toxic substances.

Benefits of technology

The uniform dispersion and stability of the coating are achieved, the construction difficulty is reduced, the corrosion resistance and environmental protection of the coating are improved, and the service life of the coating is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005146301040000091
    Figure BDA0005146301040000091
  • Figure BDA0005146301040000101
    Figure BDA0005146301040000101
Patent Text Reader

Abstract

The invention relates to the technical field of coatings, in particular to an inorganic water-based phosphate metal anti-corrosion nano coating and a preparation method thereof. The coating comprises the following components in parts by weight: 10-15 parts of cerium dioxide nanoparticles, 20-25 parts of modified waterborne polyurethane resin, 10-15 parts of phosphate, 1-4 parts of a flash rust inhibitor, 15-20 parts of filler, 1-4 parts of a dispersing agent, 2-4 parts of a defoaming agent, 1-4 parts of a flatting agent, 1-3 parts of a coalescing agent, 1-3 parts of a thickening agent and 25-45 parts of deionized water. The preparation method of the coating comprises the following steps: S1, weighing the raw materials according to the components and the parts; s2, sequentially putting the modified waterborne polyurethane resin, the deionized water, the phosphate and the anti-flash-rust agent into a stirring pot, stirring at a low speed for 10 seconds, adding water into the stirring pot, stirring at a low speed for 1-2 minutes, stirring at a high speed for 2 minutes, and standing for 20-30 minutes; s3, adding the defoaming agent, the dispersing agent, the filler and the flatting agent into the stirring pot, adding the cerium dioxide nanoparticles into the stirring pot in a low-speed stirring state, adding the coalescing agent and the thickening agent, and stirring at a high speed for 30 minutes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coatings, and more specifically to an inorganic water-based phosphate metal anticorrosive nano coating and a preparation method thereof. Background Art

[0002] Nowadays, the scale of China's nanomaterials market continues to grow. According to data from the China Research Institute, the scale of my country's nanomaterials market has climbed to 203.1 billion yuan in 2022, achieving a steady growth of 9.89% year-on-year. This growth trend indicates the broad prospects and huge market potential of the nanomaterials industry. In 2024, the market size is expected to expand further. At the same time, the upgrading of domestic industrial industries has brought new development opportunities to the industrial coatings market, promoting the accelerated iteration and upgrading of industrial coatings products and technologies, making them show an overall high-end trend. Against this background, many coatings brands have focused on the mid-to-high-end coatings market segments such as heavy anti-corrosion, anti-rust, acid and alkali resistance, and chemical resistance. Nano anti-corrosion materials have emerged and gradually emerged.

[0003] Nowadays, nano anti-corrosion coatings include environmentally friendly nano-silicon waterproof anti-corrosion coatings, nano-latex paints, etc. Among them, environmentally friendly nano-silicon waterproof anti-corrosion coatings are two-component water-emulsion elastic anti-corrosion and waterproof coating materials based on synthetic polymer materials, with nano-silicon curing agents and nano-additives added, and produced through complex processes. This kind of coating is green and environmentally friendly, non-toxic and pollution-free, the coating is elastic, easy to construct, fast drying, strong adhesion, and can self-heal concrete cracks below 0.3mm. It is mainly used for the anti-corrosion and waterproofing of concrete, such as underground integrated pipe corridors, sewage treatment plants, water plants, power plants, landfills, etc.; some products in nano latex paints have improved the performance of the coating through the addition of nanotechnology, making it have better weather resistance, scrub resistance and antibacterial properties.

[0004] At present, nano anti-corrosion coatings have the following problems: 1) Dispersibility problem. Nano-scale powder materials are extremely fine and close to molecular structure, so it is difficult to disperse them evenly in coating production. This may lead to unstable coating performance and affect the anti-corrosion effect. 2) Construction difficulty. Some nano anti-corrosion coatings have high construction conditions and technical requirements. For example, the thickness of the coating, the temperature and humidity of the construction environment, etc. need to be strictly controlled. This increases the construction difficulty and cost. 3) Environmental protection issues. Although nano anti-corrosion coatings have certain advantages in environmental protection, some products may still contain ingredients that are harmful to the environment or human body. Therefore, when selecting and using them, you need to pay attention to their environmental performance. Summary of the invention

[0005] The purpose of the present invention is to provide an inorganic water-based metal anticorrosion coating doped with nano-cerium dioxide and phosphate and a preparation method thereof, which ensures that the coating has excellent anticorrosion performance and is environmentally friendly, non-toxic and harmless, has a low content of volatile organic matter, and VOCs is 45 mg / m 3 , and the coating is easy to apply; the prepared coating has a grade 1 adhesion and no sagging. The addition of cerium dioxide nanoparticles to the coating is to improve the wear resistance and chemical stability of the coating. At the same time, the coating also has good weather resistance and aging resistance, and has a long service life. Coating on the metal surface can extend its service life by about 1 to 2 years. The wear test shows that the coating wear is 0.05g, and the surface contact angle after wear is reduced by 3.5° compared with that before wear. It is resistant to salt spray for 460 hours and resistant to aqueous solution for 400 hours. On the other hand, adding a dispersant to the coating can make the cerium dioxide nanoparticles evenly dispersed in the coating, making the performance of the coating uniform and uniform.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] The first aspect of the present invention provides an inorganic water-based phosphate metal anti-corrosion nano coating, whose components, by weight, are: 10 to 15 parts of cerium dioxide nanoparticles, 20 to 25 parts of modified water-based polyurethane resin, 10 to 15 parts of phosphate, 1 to 4 parts of anti-flash rust agent, 15 to 20 parts of filler, 1 to 4 parts of dispersant, 2 to 4 parts of defoaming agent, 1 to 4 parts of leveling agent, 1 to 3 parts of film-forming aid, 1 to 3 parts of thickener and 25 to 45 parts of deionized water.

[0008] In a preferred embodiment, the flash rust preventer is one or more of polyphosphates and nitrites; the filler is one or more of silicon micropowder, precipitated barium sulfate, and mica powder; the dispersant is one or more of polyacrylic acid derivatives, polyether derivatives, and sodium hexametaphosphate; the defoamer is one or more of defoamer SPA202 and defoamer A10; the leveling agent is one or more of polypropylene resin and pure polyacrylate leveling agent; the film-forming aid is one or more of ethylene glycol monobutyl ether, dipropylene glycol n-butyl ether, and dodecyl alcohol ester; the thickener is one or more of polyurethane, sodium polyacrylate, and polyethylene oxide.

[0009] According to a preferred embodiment, a method for preparing a modified waterborne polyurethane resin comprises the following steps:

[0010] The preparation method of the modified waterborne polyurethane resin comprises the following steps:

[0011] Sa1, take 60-70g polyether and 35-40g toluene diisocyanate and put them in a three-necked flask, open the condenser for the first sealing and stirring, and then react at 90-100°C for 2h; lower the temperature in the three-necked flask to 80°C, add 15-20g acetone and mix evenly, add 6g dimethylolpropionic acid and 1.6g trimethylolpropane, and continue to react for 2h; lower the temperature in the three-necked flask to 70°C, add 8-10g diethylene glycol and 15-20g acetone and mix evenly, add 0.01g stannous octoate as a catalyst, seal and stir for the second time, and continue to react for 2h; lower the temperature in the three-necked flask to 60°C, add 80-100g acetone and cellulose nanofibers, seal and stir for the third time, and continue to react for 1h; add 5-7g triethylamine for neutralization, neutralize for 5min-10min, obtain a neutralized prepolymer, and cool the neutralized prepolymer to room temperature;

[0012] Sa2, add 400g of water to the emulsifier, and stir with a high-speed disperser, pour the neutralized prepolymer into the emulsifier, evenly disperse it, and then distill it. The distillation time is 3min, and the temperature in the emulsifier is raised to 50°C, and then the temperature in the emulsifier is raised to 70-80°C, and then the temperature is lowered to 50°C after distillation for 1.5h to obtain an aqueous polyurethane emulsion.

[0013] More preferably, a more preferred method for preparing a modified waterborne polyurethane resin comprises the following steps:

[0014] Sa1, take 62g polyether and 40g toluene diisocyanate and put them in a three-necked flask, open the condenser for the first sealing and stirring, and react at 90°C for 2h; lower the temperature in the three-necked flask to 80°C, add 15g acetone and mix evenly, add 6g dimethylolpropionic acid and 1.6g trimethylolpropane, and continue to react for 2h; lower the temperature in the three-necked flask to 70°C, add 9.1g diethylene glycol and 15g acetone and mix evenly, add 0.01g stannous octoate as a catalyst, seal and stir for the second time, and continue to react for 2h; lower the temperature in the three-necked flask to 60°C, add 80g acetone and cellulose nanofibers, seal and stir for the third time, and continue to react for 1h; add 5.2g triethylamine for neutralization, neutralize for 5min, obtain a neutralized prepolymer, and cool the neutralized prepolymer to room temperature;

[0015] Sa2, add 400g of water to an emulsifier, and stir with a high-speed disperser, pour the neutralized prepolymer into the emulsifier, evenly disperse it, and then distill it, first raise the temperature in the emulsifier to 50°C, then raise the temperature in the emulsifier to 70°C, distill for 1.5h, and then cool it to 50°C to obtain a modified waterborne polyurethane emulsion.

[0016] More preferably, in step Sa1, the stirring rates of the first sealed stirring and the second sealed stirring are 150-200 r / min, the time of the first sealed stirring is 10 min, the time of the second sealed stirring is 2 h, the rate of the third sealed stirring is 200-250 r / min, and the time of the third sealed stirring is 1 h; in step Sa2, the stirring rate of the high-speed disperser is 350-400 r / min, and the stirring time is 30 min.

[0017] In a preferred embodiment, a more preferred method for preparing cerium dioxide nanoparticles comprises the following steps:

[0018] Sb1, dissolving Ce(NO3)3·6H2O in deionized water to obtain Ce(NO3)3 solution;

[0019] Sb2, dissolving NaOH in deionized water to obtain a NaOH solution;

[0020] Sb3, drop NaOH solution into Ce(NO3)3 solution to obtain a suspension;

[0021] Sb4. After the suspension is magnetically stirred for 30 minutes, it is placed in a stainless steel reaction kettle lined with polytetrafluoroethylene and kept warm for 24 hours at 100°C, 180°C and 100°C respectively, then cooled to room temperature, and the suspension is alternately washed with deionized water and anhydrous ethanol, and the obtained precipitate is dried in a vacuum drying oven at 60°C for 8 hours to obtain cerium dioxide nanoparticles.

[0022] More preferably, in step Sb1, the mass ratio of Ce(NO3)3·6H2O to deionized water is 1:(5-8); in step Sb2, the mass ratio of NaOH to deionized water is 1:(3-5).

[0023] More preferably, in step Sb4, the rate of the magnetic stirring is 150-200 r / min.

[0024] The second aspect of the present invention provides a method for preparing the above-mentioned inorganic water-based phosphate metal anticorrosive nano coating, comprising the following steps:

[0025] S1. Weigh the raw materials according to the above components and quantities;

[0026] S2. Put the modified waterborne polyurethane resin, deionized water, phosphate, and flash rust inhibitor into a stirring pot in order and stir at a low speed for 10 seconds. Add 25 to 45 parts of deionized water into the stirring pot, stir at a low speed for 1 to 2 minutes, stir at a high speed for 2 minutes, and then let it stand for 20 to 30 minutes.

[0027] S3. After adding defoamer, dispersant, filler and leveling agent into the stirring pot, add cerium dioxide nanoparticles into the stirring pot under low-speed stirring, and then add film-forming aid and thickener and stir at high speed for 30 minutes.

[0028] In a preferred embodiment, in steps S2 to S3, the stirring rate of the low-speed stirring is 30 to 60 r / min, and the stirring rate of the high-speed stirring is 60 to 120 r / min.

[0029] Beneficial effects of the present invention

[0030] 1. At present, there is a significant problem in the domestic metal anticorrosion nano coatings, that is, in the environment of high humidity and high temperature after coating, the solvent in the coating evaporates too quickly or water vapor accumulates on the surface of the base layer, which may cause bubbles to be generated. The inorganic water-based phosphate metal anticorrosion nano coating of the present invention uses water as a solvent, and its volatilization rate after coating is low. On the other hand, an appropriate amount of defoaming agent is added in the ratio, which effectively solves the problem of bubbles generated by too fast solvent volatilization, and has greater technical advantages compared with existing coatings.

[0031] 2. The nano-scale powder material in the anti-corrosion nano-coating is extremely fine. Due to its special molecular structure, it is difficult to disperse evenly in the coating production, which leads to the instability of the coating performance and affects the anti-corrosion effect. The inorganic water-based phosphate metal anti-corrosion nano-coating in the present invention has a dispersant added, so it has good dispersibility, and its pigment and filler can be evenly distributed in the solvent or base material, which improves the stability and consistency of the coating, and at the same time enhances the hiding power and durability of the coating, making the coating effect more ideal.

[0032] 3. The phosphate used in the anti-corrosion coating of the present invention can combine with corrosive substances such as chloride ions to form insoluble precipitates, effectively preventing corrosive substances such as chloride ions from reacting with the metal surface, thereby significantly improving the corrosion resistance of metal materials. This characteristic makes the coating have significant advantages over traditional metal anti-corrosion coatings, and can protect the metal surface from corrosion for a longer period of time. Secondly, phosphate wear-resistant coatings have strong wear resistance and can prevent the base material from being affected by friction and wear. This characteristic makes the present invention perform better in occasions that need to withstand frequent friction and wear, and can extend the service life of the coating. In addition, phosphate coatings can withstand certain high temperatures, are not easy to fall off or peel off at high temperatures, and can still maintain stable anti-corrosion properties under high temperature environments. The coating of this invention is suitable for metal parts that need to withstand high temperature tests.

[0033] 4. Most common metal anti-corrosion coatings, such as oily metal anti-corrosion coatings, contain ingredients that are harmful to the environment or human body, so it is difficult to ensure environmental protection during use. Most of the resins, solvents, fillers, and additives used in the coating of the present invention are inorganic substances. The resin adopts environmentally friendly water-based polyurethane resin. The content of organic matter or toxic substances volatile during use or storage of the coating is extremely low. Secondly, the phosphate used in the present invention is an environmentally friendly material with little impact on the environment, which is in line with the strategy of sustainable development. Compared with traditional metal anti-corrosion coatings, coatings containing phosphate components cause less pollution to the environment during production and use, which is beneficial to protecting the environment and human health. DETAILED DESCRIPTION

[0034] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0035] Detailed Overview of the Invention

[0036] The invention discloses an inorganic water-based phosphate metal anticorrosive nano coating, which comprises the following components by weight: 10 to 15 parts of cerium dioxide nanoparticles, 20 to 25 parts of modified water-based polyurethane resin, 10 to 15 parts of phosphate, 1 to 4 parts of anti-flash rust agent, 15 to 20 parts of filler, 1 to 4 parts of dispersant, 2 to 4 parts of defoamer, 1 to 4 parts of leveling agent, 1 to 3 parts of film-forming aid, 1 to 3 parts of thickener and 25 to 45 parts of deionized water.

[0037] Preferably, the flash rust inhibitor is at least one of polyphosphate and nitrite.

[0038] Preferably, the filler is at least one of silicon micropowder, precipitated barium sulfate and mica powder.

[0039] Preferably, the dispersant is at least one of polyacrylic acid derivatives, polyether derivatives, and sodium hexametaphosphate. The dispersant can effectively disperse the cerium dioxide nanoparticles uniformly in the coating, making the performance of the coating uniform and stable.

[0040] Preferably, the defoaming agent is one or more of defoaming agent SPA202 and defoaming agent A10.

[0041] Preferably, the leveling agent is at least one of polypropylene resin and pure polyacrylate leveling agent.

[0042] Preferably, the film-forming aid is one or more of ethylene glycol monobutyl ether, dipropylene glycol n-butyl ether, and dodecyl alcohol ester.

[0043] Preferably, the thickener is one or more of polyurethane, sodium polyacrylate, and polyethylene oxide.

[0044] A preferred method for preparing a modified waterborne polyurethane resin comprises the following steps: weighing 62g of polyether and 40g of toluene diisocyanate, pouring them into a dry three-necked flask, opening the condenser, sealing and stirring evenly. The reactor temperature is controlled at 90°C and reacted for 2h. The temperature of the three-necked flask is reduced to 80°C, 15g of acetone is added, and after the acetone and the reaction liquid are evenly mixed, 6g of dimethylol propionic acid and 1.6g of trimethylol propane are added, and the reaction is continued for 2h. The temperature of the three-necked flask is reduced to 70°C, 9.1g of diethylene glycol and 15g of acetone are added, and after the acetone and the reaction liquid are evenly mixed, 0.01g of stannous octoate, a catalyst, is added, sealed and stirred, and the reaction is continued for 2h. The temperature is reduced to 60°C, 80g of acetone and cellulose nanofibers are added, sealed and stirred, and the reaction is continued for 1h. In the prepolymer, 5.2g of triethylamine is added for neutralization, and the neutralization reaction is 5min. Dispersion and emulsification: Cool the obtained prepolymer to room temperature, pour 400g of water into the emulsifier, stir with a high-speed disperser, slowly pour the obtained neutralized prepolymer into it, and disperse evenly. After uniform dispersion, distill for 3 minutes. Raise the temperature to 50℃ to observe the foaming situation, continue to raise the temperature to about 70℃ and distill for 1.5h, and cool down to 50℃ to obtain a modified waterborne polyurethane emulsion.

[0045] More preferably, the modified waterborne polyurethane resin is homemade, and the homemade reference preparation method is: Du Juan. "Preparation and modification research of waterborne polyurethane resin". Qingdao University of Science and Technology, 2010.

[0046] More preferably, during the preparation of the modified waterborne polyurethane resin, the first and second sealed stirring rates are the same, 150-200 r / min, the first sealed stirring time is 10 min, and the second sealed stirring time is 2 h; the third sealed stirring rate is 200-250 r / min, and the duration is 1 h; the last time a high-speed disperser is used for stirring, the stirring rate is 350-400 r / min, and the duration is 30 min.

[0047] A preferred method for preparing cerium dioxide nanoparticles comprises the following steps: synthesizing nano CeO2 by hydrothermal method, dissolving Ce(NO3)3·6H2O in deionized water, dissolving NaOH in deionized water respectively, and then uniformly dropping the NaOH solution into the prepared Ce(NO3)3 solution. The two kinds of suspensions (Ce(NO3)3 solution and NaOH solution) formed are magnetically stirred for 30 minutes and then placed in a 50mL polytetrafluoroethylene-lined stainless steel reactor respectively, and kept in an oven at 100°C, 180°C and 100°C for 24 hours respectively, and after naturally cooling to room temperature, the suspension is alternately washed with deionized water and anhydrous ethanol, and the obtained precipitate is dried in a vacuum drying oven at 60°C for 8 hours, and finally cerium dioxide nanoparticles are obtained.

[0048] More preferably, Ce(NO3)3·6H2O is dissolved in deionized water in a mass ratio of 1:(5-8); and NaOH is dissolved in deionized water in a mass ratio of 1:(3-5).

[0049] More preferably, the magnetic stirring rate is about 150-200 r / min.

[0050] A method for preparing an inorganic water-based phosphate metal anticorrosive nano coating comprises the following steps:

[0051] The first step is to weigh the raw materials according to the above ratio.

[0052] In the second step, the modified waterborne polyurethane resin, deionized water, phosphate, and flash rust inhibitor are placed in a stirring pot in order. After slight stirring for 10 seconds (at a low speed of 30 to 60 r / min to make the materials uniform), 25 to 45 parts of deionized water are added, and the mixture is stirred at a low speed for 1 to 2 minutes, and then stirred at a high speed (60 to 120 r / min) for 2 minutes. Then, the mixture is allowed to stand for 20 to 30 minutes.

[0053] The third step is to add defoamer, dispersant, filler and leveling agent into the mixing pot, then turn on the mixer again, and slowly add cerium dioxide nanoparticles into the mixture while stirring at a low speed of 30-60 r / min. Finally, add film-forming aid and thickener and keep stirring at a high speed for 30 seconds to obtain the coating.

[0054] The present invention utilizes cerium dioxide nanoparticles added to phosphate coatings to enhance the coating's comprehensive properties such as wear resistance, weather resistance, chemical stability, etc. The prepared inorganic water-based phosphate metal anti-corrosion coating can work on rusted steel structure surfaces, greatly reducing the difficulty of engineering construction and the workload of workers, and has super strong steel structure anti-corrosion performance in C4 or even C5-M environments.

[0055] Example 1

[0056] The inorganic water-based anti-metal corrosion coating is composed, by weight, of 10 parts of cerium dioxide nanoparticles, 20 parts of modified water-based polyurethane resin, 10 parts of phosphate, 1 part of polyphosphate, 15 parts of silicon micropowder, 1 part of polyacrylic acid derivative, 2 parts of defoamer SPA202, 1 part of polypropylene resin, 1 part of ethylene glycol monobutyl ether, 1 part of polyurethane and 25 parts of deionized water.

[0057] The preparation method of modified waterborne polyurethane resin comprises the following steps: weighing 62g polyether and 40g toluene diisocyanate, pouring into a dry three-necked flask, opening the condenser, sealing and stirring evenly for 10min, and maintaining the speed at 150-200r / min. The temperature of the reactor is controlled at 90°C and reacting for 2h. The temperature of the three-necked flask is reduced to 80°C, 15g acetone is added, and after the acetone and the reaction liquid are evenly mixed, 6g dimethylol propionic acid and 1.6g trimethylol propane are added, and the reaction is continued for 2h. The temperature of the three-necked flask is reduced to 70°C, 9.1g diethylene glycol and 15g acetone are added, and after the acetone and the reaction liquid are evenly mixed, 0.01g stannous octoate as a catalyst is added, sealed and stirred, and the speed is maintained at 150-200r / min, and the reaction is continued for 2h. The temperature is reduced to 60°C, 80g acetone and cellulose nanofibers are added, sealed and stirred, and the stirring speed is 200-250r / min, and the reaction is continued for 1h to obtain a prepolymer. Add 5.2g triethylamine to the prepolymer for neutralization, and react for 5min. Dispersion and emulsification: Cool the neutralized prepolymer to room temperature, pour 400g of water into the emulsifier, stir for 30min with a high-speed disperser at a stirring rate of 350-400r / min, slowly pour the neutralized prepolymer into it and disperse evenly. After uniform dispersion, distill. Raise the temperature to 50℃ to observe the foaming, continue to raise the temperature to about 70℃ and distill for 1.5h, then cool to 50℃ to obtain a waterborne polyurethane emulsion.

[0058] The preparation method of cerium dioxide nanoparticles comprises the following steps: synthesizing nano CeO2 by hydrothermal method, dissolving Ce(NO3)3·6H2O in deionized water, dissolving NaOH in deionized water respectively, and then uniformly dropping the solution into the prepared cerium solution. The three suspensions formed are magnetically stirred for 30 minutes at a rate of about 150-200 r / min, and after magnetic stirring, they are respectively placed in a 50mL polytetrafluoroethylene-lined stainless steel reactor, and kept in an oven at 100°C, 180°C and 100°C for 24 hours, and after naturally cooling to room temperature, the suspension is alternately washed with deionized water and anhydrous ethanol, and the obtained precipitate is dried in a vacuum drying oven at 60°C for 8 hours, and finally cerium dioxide nanoparticles are obtained.

[0059] Wherein, Ce(NO3)3·6H2O is dissolved in deionized water in a mass ratio of 1:(5-8); NaOH is dissolved in deionized water in a mass ratio of 1:(3-5).

[0060] The preparation method of inorganic water-based phosphate metal anticorrosive nano coating comprises the following steps:

[0061] The first step is to weigh the raw materials according to the ratio provided in this embodiment.

[0062] In the second step, the modified waterborne polyurethane resin, deionized water, phosphate and anti-flash rust agent are placed in a stirring pot in order, and after slight stirring for 10 seconds (at a low speed of 30 to 60 r / min to make the materials uniform), water is added, and stirring is continued at a low speed for 1 to 2 minutes, and then at a high speed (60 to 120 r / min) for 2 minutes, and then allowed to stand for 20 to 30 minutes.

[0063] The third step is to add defoamer, dispersant, filler and leveling agent into the mixing pot, then turn on the mixer again, and slowly add cerium dioxide nanoparticles into the mixture while stirring at a low speed of 30-60 r / min. Finally, add film-forming aid and thickener and keep stirring at a high speed for 30 seconds to obtain the coating.

[0064] Example 2

[0065] In this embodiment, the inorganic water-based phosphate metal anti-corrosion nano coating and its preparation method are basically the same as those in Example 1, except that the coating is composed, by weight, of 11 parts of cerium dioxide nanoparticles, 21 parts of modified water-based polyurethane resin, 11 parts of phosphate, 2 parts of polyphosphate, 16 parts of silicon micropowder, 2 parts of polyacrylic acid derivative, 22.5 parts of defoaming agent SPA202, 2 parts of polypropylene resin, 1.5 parts of ethylene glycol monobutyl ether, 1.5 parts of polyurethane, and 30 parts of deionized water.

[0066] The preparation methods of cerium dioxide nanoparticles and modified waterborne polyurethane resin are the same as those in Example 1.

[0067] Example 3

[0068] In this embodiment, the inorganic water-based phosphate metal anti-corrosion nano coating and its preparation method are basically the same as those in Example 1, except that the coating, by weight, is composed of: 12 parts of cerium dioxide nanoparticles, 22 parts of modified water-based polyurethane resin, 12 parts of phosphate, 2.5 parts of polyphosphate, 17 parts of precipitated sulfuric acid, 2.5 parts of polyether derivative, 3 parts of defoamer SPA202, 2.5 parts of polypropylene resin, 2 parts of dipropylene glycol n-butyl ether, 2 parts of sodium polyacrylate, and 35 parts of deionized water.

[0069] The preparation methods of cerium dioxide nanoparticles and modified waterborne polyurethane resin are the same as those in Example 1.

[0070] Example 4

[0071] In this embodiment, the inorganic water-based phosphate metal anticorrosion nano coating and its preparation method are basically the same as those in Example 1, except that the coating, by weight, is composed of: 13 parts of cerium dioxide nanoparticles, 23 parts of modified water-based polyurethane resin, 13 parts of phosphate, 3 parts of nitrite, 18 parts of precipitated barium sulfate, 3 parts of polyether derivative, 3.5 parts of defoamer A10, 3 parts of pure polyacrylate leveling agent, 2.5 parts of dipropylene glycol n-butyl ether, 2.5 parts of sodium polyacrylate, and 40 parts of deionized water.

[0072] The preparation methods of cerium dioxide nanoparticles and modified waterborne polyurethane resin are the same as those in Example 1.

[0073] Example 5

[0074] In this embodiment, the inorganic water-based phosphate metal anti-corrosion nano coating and its preparation method are basically the same as those in Example 1, except that the coating is composed, by weight, of 15 parts of cerium dioxide nanoparticles, 25 parts of modified water-based polyurethane resin, 15 parts of phosphate, 4 parts of nitrite, 20 parts of mica powder, 4 parts of sodium hexametaphosphate, 4 parts of defoaming agent A10, 4 parts of pure polyacrylate, 3 parts of dodecyl alcohol ester, 3 parts of polyethylene oxide, and 45 parts of deionized water.

[0075] The preparation methods of cerium dioxide nanoparticles and modified waterborne polyurethane resin are the same as those in Example 1.

[0076] Comparative Example 1

[0077] In this comparative example, the inorganic water-based anti-metal corrosion coating and its preparation method are substantially the same as those in Example 1, except that the modified water-based polyurethane resin is replaced by a water-based polyurethane resin.

[0078] The preparation method of cerium dioxide nanoparticles is the same as that in Example 1.

[0079] Comparative Example 2

[0080] In this comparative example, the inorganic water-based anti-metal corrosion coating and its preparation method are substantially the same as those in Example 1, except that no cerium dioxide nanoparticles are added to the coating.

[0081] The coatings prepared in the above Examples 1 to 5 and Comparative Examples 1 to 2 were subjected to relevant performance tests, and the test methods and test results are shown in Table 1 below.

[0082] Table 1. Performance test table of inorganic water-based anti-metal corrosion coating of the present invention

[0083]

[0084]

[0085] It can be seen from Table 1 that, compared with Comparative Examples 1 to 2, the inorganic water-based phosphate metal anticorrosion nano coatings of Examples 1 to 5 of the present invention have higher adhesion, better moisture and heat resistance, salt spray resistance, and greater hardness.

[0086] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. An inorganic water-based phosphate metal anticorrosion nano coating, characterized in that: The components are as follows by weight: 10 to 15 parts of cerium dioxide nanoparticles, 20 to 25 parts of modified waterborne polyurethane resin, 10 to 15 parts of phosphate, 1 to 4 parts of anti-flash rust agent, 15 to 20 parts of filler, 1 to 4 parts of dispersant, 2 to 4 parts of defoaming agent, 1 to 4 parts of leveling agent, 1 to 3 parts of film-forming aid, 1 to 3 parts of thickener and 25 to 45 parts of deionized water.

2. According to claim 1, the inorganic water-based phosphate metal anticorrosion nano coating is characterized in that: The preparation method of the modified waterborne polyurethane resin comprises the following steps: Sa1, take 60-70g polyether and 35-40g toluene diisocyanate and put them in a three-necked flask, open the condenser for the first sealing and stirring, and then react at 90-100°C for 2h; lower the temperature in the three-necked flask to 80°C, add 15-20g acetone and mix evenly, add 6g dimethylolpropionic acid and 1.6g trimethylolpropane, and continue to react for 2h; lower the temperature in the three-necked flask to 70°C, add 8-10g diethylene glycol and 15-20g acetone and mix evenly, add 0.01g stannous octoate as a catalyst, seal and stir for the second time, and continue to react for 2h; lower the temperature in the three-necked flask to 60°C, add 80-100g acetone and cellulose nanofibers, seal and stir for the third time, and continue to react for 1h; add 5-7g triethylamine for neutralization, neutralize for 5min-10min, obtain a neutralized prepolymer, and cool the neutralized prepolymer to room temperature; Sa2, add 400g of water to the emulsifier, and stir with a high-speed disperser, pour the neutralized prepolymer into the emulsifier, evenly disperse it, and then distill it. The distillation time is 3min, and the temperature in the emulsifier is raised to 50°C, and then the temperature in the emulsifier is raised to 70-80°C, and then the temperature is lowered to 50°C after distillation for 1.5h to obtain an aqueous polyurethane emulsion.

3. The inorganic water-based phosphate metal anticorrosion nano coating according to claim 1, characterized in that: The flash rust prevention agent is one or more of polyphosphates and nitrites; the filler is one or more of silicon micropowder, precipitated barium sulfate, and mica powder; the dispersant is one or more of polyacrylic acid derivatives, polyether derivatives, and sodium hexametaphosphate; the defoamer is one or more of defoamer SPA202 and defoamer A10; the leveling agent is one or more of polypropylene resin and pure polyacrylate leveling agent; the film-forming aid is one or more of ethylene glycol monobutyl ether, dipropylene glycol n-butyl ether, and dodecyl alcohol ester; the thickener is one or more of polyurethane, sodium polyacrylate, and polyethylene oxide.

4. The inorganic water-based phosphate metal anticorrosion nano coating according to claim 3, characterized in that: In step Sa1, the stirring rates of the first sealed stirring and the second sealed stirring are 150-200 r / min, the time of the first sealed stirring is 10 min, the time of the second sealed stirring is 2 h, the rate of the third sealed stirring is 200-250 r / min, and the time of the third sealed stirring is 1 h; in step Sa2, the stirring rate of the high-speed disperser is 350-400 r / min, and the stirring time is 30 min.

5. The inorganic water-based phosphate metal anticorrosion nano coating according to claim 1, characterized in that: The method for preparing the cerium dioxide nanoparticles comprises the following steps: Sb1, dissolving Ce(NO3)3·6H2O in deionized water to obtain a cerium solution; Sb2, dissolving NaOH in deionized water to obtain a NaOH solution; Sb3, dropping NaOH solution into cerium solution to obtain suspension; Sb4. After the suspension is magnetically stirred for 30 minutes, it is placed in a stainless steel reaction kettle lined with polytetrafluoroethylene and kept warm for 24 hours at 100°C, 180°C and 100°C respectively, then cooled to room temperature, and the suspension is alternately washed with deionized water and anhydrous ethanol, and the obtained precipitate is dried in a vacuum drying oven at 60°C for 8 hours to obtain cerium dioxide nanoparticles.

6. The inorganic water-based phosphate metal anticorrosion nano coating according to claim 5, characterized in that: In step Sb1, the mass ratio of Ce(NO3)3·6H2O to deionized water is 1:(5-8); in step Sb2, the mass ratio of NaOH to deionized water is 1:(3-5).

7. The inorganic water-based phosphate metal anticorrosion nano coating according to claim 5, characterized in that: In step Sb4, the rate of the magnetic stirring is 150-200 r / min.

8. A method for preparing the inorganic water-based phosphate metal anticorrosion nano coating according to any one of claims 1 to 7, characterized in that: The steps include: S1. Weigh the raw materials according to the components and quantities described in claim 1; S2. Put the modified waterborne polyurethane resin, deionized water, phosphate, and flash rust inhibitor into a stirring pot in order and stir at a low speed for 10 seconds. Add 25 to 45 parts of deionized water into the stirring pot, stir at a low speed for 1 to 2 minutes, stir at a high speed for 2 minutes, and then let it stand for 20 to 30 minutes. S3. After adding defoamer, dispersant, filler and leveling agent into the stirring pot, add cerium dioxide nanoparticles into the stirring pot under low-speed stirring, and then add film-forming aid and thickener and stir at high speed for 30 minutes.

9. The method for preparing the inorganic water-based phosphate metal anticorrosive nano coating according to claim 8, characterized in that: In steps S2 to S3, the stirring rate of the low-speed stirring is 30 to 60 r / min, and the stirring rate of the high-speed stirring is 60 to 120 r / min.